In – vitro antioxidant activity of leaves on Datura stramonium, L.and Datura metal, L. Solanaceae – A comparative studies - Veeraragavan, Anburajan.; Jahabar Ali, ,Hameed Sultan Sheik; Ismail, Abdul Hathi. Mohamed (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
The ethanol extracts of Datura stramonium and Datura metel (Family: Solanaceae) collected from Pappakovil, Nagapattinam Dist of Tamil Nadu, India. The Ethanol extract obtained by maceration extraction was examined for its antioxidant activities. The antioxidant activity was determined by means of the DPPH radical scavenging test, Total antioxidant (TAA) and superoxide anion scavenging activity assay (SASA).Result from three methods indicate that the antioxidant activity of D. stramonium and D. metel of ethanol extracts were time and concentration dependent. The antioxidant potential of D. stramonium and D. metel determined by the DPPH method expressed as IC50 was The half inhibition concentration (IC50) of plant extracts D. stramonium , D. metel and ascorbic acid were 49.72 µg ml-1, 50.35µg ml-1 and 34.91 µg ml-1 respectively. the antioxidant potential of D. stramonium and D. metel determined by the Total antioxidant assay (TAA) method expressed as IC50 was The half inhibition concentration (IC50) of D. stramonium , D. metel and ascorbic acid were 49.59µg ml-1, 49.94µg ml-1 and 42.41 µg ml-1 respectively. the antioxidant potential of D. stramonium and D. metel from determined by the Superoxide anion scavenging activity assay (SASA) method expressed as IC50 was The half inhibition concentration (IC50) of D. stramonium and D. metel were, 49.58 and 49.73µg ml-1 andascorbic acid were 31.62µg ml-1 respectively.